Determinación de la eficacia del ácido giberélico (Progibb 40wg)sobre el rendimiento y la calidad de la caña de azúcar (Saccharum spp.) var. NA 56-42 en Liberia, Guanacaste, Costa Rica - Kopper-Sandoval, Juan Carlos (Instituto Tecnológico de Costa Rica, 2015)
Research was conducted at the Central Azucarera Tempisque S.A (CATSA) in Guardia Liberia, Costa Rica, in order to evaluate the effectiveness of gibberellic acid on improving the quality and yield of cultivation of sugarcane (Saccharum spp). var. NA 56-42. Four treatments were evaluated using a completely randomized design (RCBD) with five replicates, two of which comprised two increasing doses of ProGibb® 40 WG 10 g PC / ha, and ProGibb® 40 WG 20 g PC / ha, a third was consisting of ProGibb® 40 WG at doses of 10 g PC / ha mixed with foliar fertilizers and finally commercial control; two complete applications for treatment at 59 and 144 days after the first harvest took place. The results showed that applications to perform treatments with ProGibb® 40 WG in their respective doses and mixed with foliar fertilizers at two frequencies on sugar cane plants , no statistics responses were determined in the variables analyzed for development, growth, crop yield (53,03 t/ha) and quality indicators from sugar cane juice.
Proyecto de graduación (Licenciatura en Ingeniería en Agronomía) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Agronomía, 2015
Keywords: Ácido giberélico; Jugo de la caña de azúcar; Calidad; Rendimiento